A vision for regular, rapid assessments of the tropical northwestern Atlantic’s coral reefs - Lang, Judith C. (2006)
The Atlantic and Gulf Rapid Reef Assessment (AGRRA) Program, consisting of non-fixed, transectbased visual surveys, provides “snapshot” characterizations of a number of structurally or functionally important benthic and fish indicators on tropical northwestern Atlantic (TNWA) coral reefs and Brazil. To ameliorate the confounding factors inherent in multiyear temporal variation, a region-wide collaborative program for conducting rapid reef assessments at regular (five-year) intervals in sites that are representative of each sub-region of the TNWA is proposed. Member institutions of the Association of Marine Laboratories of the Caribbean (AMLC) and individual colleagues are invited to join in developing the vision. Rev. Biol. Trop. 54 (Suppl. 3): 23-29. Epub 2007 Jan. 15.